The role of TGR5 as an onco-immunological biomarker in tumor staging and prognosis by encompassing the tumor microenvironment - Guan, Zhiyuan; Luo, Liying; Liu, Shengfu; Guan, Zhiqiang; Zhang, Qinggang; Wu, Zhong; Tao, Kun (Frontiers in Oncology, 2022)
The relationship between G protein-coupled bile acid receptor 1 (TGR5, GPBAR1) and specifically cancer has been studied in vivo and vitro experiments, but there is still a lack of pan-cancer analysis to understand the prognostic significance and functioning mechanism of TGR5 in different cancer-driving oncogenic processes. Here we used Gene Expression Integration (GEO), Human Protein Atlas (HPA) and The Cancer Genome Atlas (TCGA) to perform pan-cancer analysis of the role of TGR5 in all 33 tumors. In all TCGA tumors, the TGR5 gene expression has been assessed and we found that highly TGR5 gene expression in most cancers is associated with poor prognosis of overall survival (OS) for cancers such as GBM (P=0.0048), KIRP (P=0.033), LGG (P=0.0028), THYM (P=0.048) and UVM (P=0.004) and then the lower expression of TGR5 was linked with poor prognosis in CESC (P=0.014), MESO (P=0.048), SARC (P=0.018) and SKCM (P=0.0085). TGR5 expression was linked with immune infiltration level of macrophage M2_TIDE and also associated with DNA methylation in ovarian and breast cancer. Regulation of hormone secretion, Rap1 pathway, osteoclast differentiation and bile acid pathway were involved in the functional mechanism of TGR5. Besides, gene expression were different in different tumor by detect RT-PCR and cell activity experiments have also found that TGR5 can increase the activity of renal cell carcinoma and reduce the activity of skin cancer and osteosarcoma cells. In this investigation, the aim was to assess the comprehensive overview of the oncogenic roles of TGR5 in all TCGA tumors using pan-analysis.